(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article describes the units used in pre-planting work on newly plowed land, which perform some operations sequentially and combine several operations and increase the yield of units by reducing fuel consumption and other costs by reducing the number of field transitions, improving the quality of soil cultivation and preventing moisture loss in it, Information on the advantages of combined aggregates and combined aggregates that allow timely planting and harvesting of crops are given.